The Application of Solar Energy in the Crops Drying Process - Abbass Z. Salman; Mohammed A. Fayad (Tikrit Journal of Engineering Sciences, 2011)
In the present study two convective types of solar dryers were investigated and tested under the Iraqi climate conditions. The first is called indirect type which consists of solar collector and drying chamber and the second type is a direct solar dryers. A drying equation based on a thin layer-drying function has been introduced to simulate the change of moisture content of crops with time taking into account the effect of flow rate of air, drying temperature, humidity ratio, initial and final moisture contents, and crops distribution on the drying rate and can be used for different crops. The dryers were tested using potato, fruit, any vegetables and other kinds of green leaves under typical condition of Iraqi weather. Good agreement has been obtained between the present results and the available published measurements. The study indicates that the indirect solar dryer gives definite performance advantage compared with the direct solar dryer.